2022
DOI: 10.1001/jamanetworkopen.2022.0348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Portal Messaging With Embedded Asynchronous Care on Physician-Assisted Smoking Cessation Attempts

Abstract: IMPORTANCE Despite the substantial health and financial burdens of smoking and the availability of effective, evidence-based interventions in primary care settings, few smokers and physicians use these strategies for smoking cessation. OBJECTIVE To evaluate whether electronic outreach to smokers with embedded asynchronous care increases the number of quit attempts and explore the roles of the message sender (ie, primary care physician [PCP] vs health care system) and patient-related characteristics. DESIGN, SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Though few prior studies have evaluated automated delivery of cessation treatment from a patient’s own PCP, studies that have (including from our own group) have shown clinical benefit. For example, in one prior trial, asynchronous cessation care provided by one’s PCP via patient portals doubled quit rates compared to portal messaging delivering standard advice to quit [ 19 ]. Thus, cessation treatment approaches delivered in an automated fashion via the EHR from a patient’s own PCP could help to address barriers to receipt of cessation treatment and improve cessation outcomes for primary care patients.…”
Section: Introductionmentioning
confidence: 99%
“…Though few prior studies have evaluated automated delivery of cessation treatment from a patient’s own PCP, studies that have (including from our own group) have shown clinical benefit. For example, in one prior trial, asynchronous cessation care provided by one’s PCP via patient portals doubled quit rates compared to portal messaging delivering standard advice to quit [ 19 ]. Thus, cessation treatment approaches delivered in an automated fashion via the EHR from a patient’s own PCP could help to address barriers to receipt of cessation treatment and improve cessation outcomes for primary care patients.…”
Section: Introductionmentioning
confidence: 99%